Golden years, silver fears - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Given the general decline in birth rates in developed nations, retirement planning is being increasingly discussed by both academics and government officials. Ralston asserts that policy makers need to start thinking about striking a balance between the citizen’s personal responsibility for retirement savings, and what the government should do.